PENGAMBILAN KEPUTUSAN MENJADI PEKERJA MIGRAN INDONESIA PEREMPUAN - Nurul Aeni (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2019)
ENGLISHDecision of being woman migrant workers brings both positive and negative consequeces for the woman workers as well as their families live behind. This study aimed: (1) to describe the decision making of being migrant workers among the applicants of woman migrant workers from Pati District; (2) to explain the factors correlate to the migrate decision making, and (3) to explain factors correlate to destination country choosing. It used quantitave approach. The primary data were obtained by spreading questionnaires among women migrant worker applicants at four labour supply companies. Meanwhile the secondary data get through desk review. Then, the data were analysed descriptively using chi square and correspondence analysis. The study resulted: (1) economic was the main factor of decision making for being woman migrant workers; (2) the factors correlated to the decision making for being woman migrant workers were the position in household, previous income, and decision making process; (3) high salary was the main factor on choosing the destination country. The factors correlated to destination country preferences were: the reasons for choosing the destination countries, age, previous job, previous salary, and husband’s age. INDONESIAKeputusan menjadi pekerja migran perempuan dapat berkonsekuensi positif maupun negatif bagi pekerja migran maupun keluarga yang ditinggalkan. Penelitian ini bertujuan: (1) menggambarkan pengambilan keputusan menjadi pekerja migran perempuan pada calon pekerja migran di Kabupaten Pati; (2) mendeskripsikan faktor yang berhubungan dengan pengambilan keputusan; dan (3) mendeskripsikan faktor yang berhubungan dengan pemilihan negara tujuan. Penelitian menggunakan pendekatan kuantitatif. Data primer didapatkan melalui pengisian kuesioner oleh para calon pekerja migran perempuan di empat PPTKIS. Sementara data sekunder didapatkan melalui review penelitian terdahulu dan dokumen yang relevan. Data yang diperoleh dianalisis secara deskriptif menggunakan chi square dan analisis korespondensi. Hasil penelitian adalah: (1) ekonomi adalah faktor utama pengambilan keputusan menjadi pekerja migran perempuan; (2) faktor yang berhubungan dengan pengambilan keputusan menjadi pekerja migran adalah posisi dalam rumah tangga, pendapatan sebelumnya, dan proses pengambilan keputusan; (3) gaji yang tinggi merupakan alasan utama pemilihan negara tujuan migrasi. Adapun faktor yang berhubungan dengan pemilihan negara tujuan migrasi adalah alasan pemilihan negara, usia, pekerjaan sebelumnya, pendapatan sebelumnya, dan usia suami.